2010
DOI: 10.3233/jad-2010-100306
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Calcium Signaling, Mitochondrial Dysfunction, and Alzheimer's Disease

Abstract: Alzheimer disease (AD) is the most common neurodegenerative disorder that affects millions of ageing people worldwide. AD is characterized by extensive synaptic and neuronal loss which lead to impaired memory and cognitive decline. The cause of pathology in AD is not completely understood and no effective therapy so far has been developed. The accumulation of toxic amyloid-beta 42 (Aβ42) peptide oligomers and aggregates in AD brain has been proposed to be primarily responsible for the pathology of the disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 124 publications
4
96
0
Order By: Relevance
“…These initial results were recapitulated experimentally in various model systems expressing FAD-related mutations in PS and the data suggested that in addition to contributing to altered γ-secretase function, PS mutations had a significant impact on Ca 2+ signalling in AD models. These early observations supported the "Ca 2+ hypothesis of AD" which states that deranged Ca 2+ signaling plays an important role in AD pathogenesis [30][31][32][33]36,37].…”
Section: Presenilins and Intracellular Calcium Signalingsupporting
confidence: 62%
“…These initial results were recapitulated experimentally in various model systems expressing FAD-related mutations in PS and the data suggested that in addition to contributing to altered γ-secretase function, PS mutations had a significant impact on Ca 2+ signalling in AD models. These early observations supported the "Ca 2+ hypothesis of AD" which states that deranged Ca 2+ signaling plays an important role in AD pathogenesis [30][31][32][33]36,37].…”
Section: Presenilins and Intracellular Calcium Signalingsupporting
confidence: 62%
“…In aging neurons, however, calcium fluxes become less controlled, leading to calcium overload (115). This excess calcium is associated with increased ROS/RNS production, mitochondrial dysfunction, and ultimately cell death (178). Many neurodegenerative diseases implicate loss of calcium regulation as a molecular basis of disease.…”
Section: A Cytoplasmic Sources Of Rosmentioning
confidence: 99%
“…Neuronal Ca 2+ is normally stored in membrane compartments such as ER, mitochondria, nuclear envelope and neurotransmitter vesicles (Verkhratsky & Petersen, 1998). Compromise of these membranebounded organelles results in a loss of homeostatic intracellular Ca 2+ control, another prominent chemical lesion in AD pathogenesis (LaFerla, 2002;Supnet & Bezprozvanny, 2010). Cytoplasmic Ca 2+ is a pivotal neuronal signal regulating multiple intraneuronal activities, neural functions and synaptic plasticity.…”
Section: Lysosome-derived Chemical Lesions and Subcellular Damagementioning
confidence: 99%